Femtosecond-resolved ablation dynamics of Si in the near field of a small dielectric particle - Kühler, Paul; Puerto, Daniel; Mosbacher, Mario; Leiderer, Paul; Garcia de Abajo, Francisco Javier; Siegel, Jan; Solis, Javier (Beilstein Journal of Nanotechnology, 2013)
In this work we analyze the ablation dynamics of crystalline Si in the intense near field generated by a small dielectric particle located at the material surface when being irradiated with an infrared femtosecond laser pulse (800 nm, 120 fs). The presence of the particle (7.9 μm diameter) leads to a strong local enhancement (ca. 40 times) of the incoming intensity of the pulse. The transient optical response of the material has been analyzed by means of fs-resolved optical microscopy in reflection configuration over a time span from 0.1 ps to about 1 ns. Characteristic phenomena like electron plasma formation, ultrafast melting and ablation, along with their characteristic time scales are observed in the region surrounding the particle. The use of a time resolved imaging technique allows us recording simultaneously the material response at ordinary and large peak power densities enabling a direct comparison between both scenarios. The time resolved images of near field exposed regions are consistent with a remarkable temporal shift of the ablation onset which occurs in the sub-picosend regime, from about 500 to 800 fs after excitation.
Keywords: crystalline Si; fs-resolved microscopy; laser ablation; near-field enhancement; ultrafast dynamics